What is the contribution of physician associates in hospital care in England? A mixed methods, multiple case study. Issue 1 (30th January 2019) - Drennan, Vari M; Halter, Mary; Wheeler, Carly; Nice, Laura; Brearley, Sally; Ennis, James; Gabe, Jonathan; Gage, Heather; Levenson, Ros; de Lusignan, Simon; Begg, Phil; Parle, James
Abstract : Objectives: To investigate the deployment of physician associates (PAs); the factors supporting and inhibiting their employment and their contribution and impact on patients' experience and outcomes and the organisation of services. Design: Mixed methods within a case study design, using interviews, observations, work diaries and documentary analysis. Setting: Six acute care hospitals in three regions of England in 2016–2017. Participants: 43 PAs, 77 other health professionals, 28 managers, 28 patients and relatives. Results: A key influencing factor supporting the employment of PAs in all settings was a shortage of doctors. PAs were found to be acceptable, appropriate and safe members of the medical/surgical teams by the majority of doctors, managers and nurses. They were mainly deployed to undertake inpatient ward work in the medical/surgical team during core weekday hours. They were reported to positively contribute to: continuity within their medical/surgical team, patient experience and flow, inducting new junior doctors, supporting the medical/surgical teams' workload, which released doctors for more complex patients and their training. The lack of regulation and attendant lack of authority to prescribe was seen as a problem in many but not all specialties. The contribution of PAs to productivity and patient outcomes was not quantifiable separately from other members of the team and wider service organisation. Patients and relatives described PAs positively but most did not understand who and what a PA was, often mistaking them for doctors. Conclusions: This study offers new insights concerning the deployment and contribution of PAs in medical and surgical specialties in English hospitals. PAs provided a flexible addition to the secondary care workforce without drawing from existing professions. Their utility in the hospital setting is unlikely to be completely realised without the appropriate level of regulation and authority to prescribe medicines and order ionising radiation within their scope of practice.